2020
DOI: 10.3390/nu12113530
|View full text |Cite
|
Sign up to set email alerts
|

PROFAST: A Randomized Trial Assessing the Effects of Intermittent Fasting and Lacticaseibacillus rhamnosus Probiotic among People with Prediabetes

Abstract: Both intermittent fasting and specific probiotics have shown promise in improving glucose tolerance with a potential for synergistic effects through alterations to gut microbiota. In this randomized, double-blinded, two-arm feasibility study, we investigated whether intermittent fasting, supplemented with Lacticaseibacillus rhamnosus HN001 probiotic, reduces HbA1c in individuals with prediabetes. All participants with HbA1c 40–50 mmol/mol commenced intermittent fasting (2 days per week of calorie restriction t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(79 citation statements)
references
References 38 publications
0
64
0
Order By: Relevance
“…Although previous studies have shown that probiotics can improve cholesterol levels in patients with type 2 diabetes (56), they have not been confirmed in patients with pre-diabetes (33,35,38). Naito et al (35) found that after 8 weeks of intervention, the blood lipid level in the probiotics group and the placebo group increased from baseline, and did not return to baseline after elution.…”
Section: Effects Of Probiotics On Pre-diabetesmentioning
confidence: 94%
See 1 more Smart Citation
“…Although previous studies have shown that probiotics can improve cholesterol levels in patients with type 2 diabetes (56), they have not been confirmed in patients with pre-diabetes (33,35,38). Naito et al (35) found that after 8 weeks of intervention, the blood lipid level in the probiotics group and the placebo group increased from baseline, and did not return to baseline after elution.…”
Section: Effects Of Probiotics On Pre-diabetesmentioning
confidence: 94%
“…Meanwhile, homoeostasis model assessment for insulin resistance (HOMA-IR) and β-cell function (HOMA-β) were not found to be different between the probiotics group and the placebo group ( 35 , 54 ). Recently, a study including 26 pre-diabetic patients demonstrated no statistically significant difference observed between the probiotic and placebo groups regarding HbA 1 c, FPG, fasting insulin or c-peptide ( 38 ).…”
Section: Study Identificationmentioning
confidence: 99%
“…[ 25 ]. Tay et al investigated the effect Lacticaseibacillus rhamnosus had among 33 participants with pre-DM [ 26 ]. The probiotic supplement of Lacticaseibacillus rhamnosus , administered for 12 weeks, showed a reduction of most DM-related values, such as haemoglobin A1c and weight, compared to the baseline but not between the intervention and control group.…”
Section: Resultsmentioning
confidence: 99%
“…FMD has been recently tested in the research of prediabetic and diabetic treatment and has shown immense therapeutic potential particularly for controlling dyslipidemia, but there are still some de ciencies regarding it effects on the glucose metabolism [10,12,15,28]. Here, we investigated the effects of FMD and UC-MSC infusion on DIO type 2 diabetic mice and discovered that FMD indeed reduced weight gain and restored the lipid metabolism, but its capacity of controlling blood glucose was questionable.…”
Section: Discussionmentioning
confidence: 99%